IMPLICATION OF CRIMINAL DETENTION IN CRIMINAL JUSTICE SYSTEM - Aras, Firman (Universitas Tadulako, 2019)
The problem in this study is how the implications of detention of defendants in the criminal justice system and how law enforcement authorities are in detention of defendants in the criminal justice system. The purpose of this study is to find out and analyze the implications of detention of defendants in the criminal justice system and to know and analyze the authority of law enforcement in the detention of defendants in the criminal justice system. The method used in this study is normative juridical. From the results of the study, it was concluded that the implication of the detention of an unlawful defendant was one form of restraint of freedom of movement, so it must be carried out according to the provisions of the criminal procedural law regarding the legal condition of detention of the accused. The implication of illegal detention of the accused will bring juridical consequences to officials who carry out detention in the form of demands for compensation and rehabilitation by defendants who are subject to unlawful detention through pre-trial authorities and/or law enforcers can issue detainees and/or defendants if the sentencing decision is dropped by the court against detainees has permanent legal force in the criminal justice system. In addition,Â the authority referred to on the basis of the period of detention that is carried out under the Criminal Code.Â Â